2019
DOI: 10.15580/gjas.2019.2.022819041
|View full text |Cite
|
Sign up to set email alerts
|

The Nutritional Composition of Local Rice Varieties in Guyana

Abstract: Rice is one of the most popular cereals worldwide, one of Guyana's major staple foods produced and consumed. With most of the population dependent on rice as a significant part of their diet, it becomes critical to analyze and monitor its composition. This project was aimed at comparatively analyzing four different local rice varieties cultivated in Guyana and one candidate line for proximate chemical components, vitamins and mineral elements. 2kg of paddy of each variety/line was harvested from pre-basic plot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Ash: Ash content of little millet flour was 1.75 g/100 grams which were found to be similar to the ash content of wheat [15]. The ash content of little millet was found to be higher than the rice [18]. Diversifying the millet consumption can thus help in alleviating hidden hunger proficiently.…”
Section: Moisturementioning
confidence: 61%
“…Ash: Ash content of little millet flour was 1.75 g/100 grams which were found to be similar to the ash content of wheat [15]. The ash content of little millet was found to be higher than the rice [18]. Diversifying the millet consumption can thus help in alleviating hidden hunger proficiently.…”
Section: Moisturementioning
confidence: 61%
“…Zhao et al [34] indicated that the GS9 gene on Chromosome 9 acts as a transcriptional activator to regulate rice grain protein content and appearance quality. Singh and Singh [35] found genotypic variation in protein content percentage among different rice varieties. The application of nitrogen fertilizer significantly increased the contents of protein over the control treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there was a great variation among the rice cultivars in nitrogen content in milled grains. It might be due to the genetic diversity of rice varieties in the mineral contents of rice grains (Singh and Singh, 2019).…”
Section: Discussionmentioning
confidence: 99%